Characterization of nitrated sugar alcohols by atmospheric‐pressure chemical‐ionization mass spectrometry. (12th January 2017) - Ostrinskaya, Alla; Kelley, Jude A.; Kunz, Roderick R.
Abstract : Rationale: The nitrated sugar alcohols mannitol hexanitrate (MHN), sorbitol hexanitrate (SHN) and xylitol pentanitrate (XPN) are in the same class of compounds as the powerful military‐grade explosive pentaerythritol tetranitrate (PETN) and the homemade explosive erythritol tetranitrate (ETN) but, unlike for PETN and ETN, ways to detect MHN, SHN and XPN by mass spectrometry (MS) have not been fully investigated. Methods: Atmospheric‐pressure chemical‐ionization mass spectrometry (APCI‐MS) was used to detect ions characteristic of nitrated sugar alcohols. APCI time‐of‐flight mass spectrometry (APCI‐TOF MS) and collision‐induced dissociation tandem mass spectrometry (CID MS/MS) were used for confirmation of each ion assignment. In addition, the use of the chemical ionization reagent dichloromethane was investigated to improve sensitivity and selectivity for detection of MHN, SHN and XPN. Results: All the nitrated sugar alcohols studied followed similar fragmentation pathways in the APCI source. MHN, SHN and XPN were detectable as fragment ions formed by the loss of NO2, HNO2, NO3, and CH2 NO2 groups, and in the presence of dichloromethane chlorinated adduct ions were observed. It was determined that in MS/MS mode, chlorinated adducts of MHN and SHN had the lowest limits of detection (LODs), while for XPN the lowest LOD was for the [XPN–NO2 ] – fragment ion. Partially nitrated analogs of each of the three compounds were also present in the starting materials, and ions attributable to these compounds versus those formed from in‐source fragmentation of MHN, SHN, and XPN were distinguished and assigned using liquid chromatography APCI‐MS and ESI‐MS. Conclusions: The APCI‐MS technique provides a selective and sensitive method for the detection of nitrated sugar alcohols. The methods disclosed here will benefit the area of explosives trace detection for counterterrorism and forensics. Copyright © 2016 John Wiley & Sons, Ltd.